Madness of Main Character, David In Dave Pelzer's Trilogy : A Child Called It, The Lost Boy, and A Man Named Dave - Sari, Yolanda Mega; Sari, Dewi Purnama (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2019)
This paper was aimed to find out the indicators of madness experienced by David and the effects of madness in David’s character through himself in A Child Called It, The Lost Boy, and A Man Named Dave trilogy. The data was collected from A Child Called It, The Lost Boy, and A Man Named Dave trilogy by Dave Pelzer. Then, The data of this study were analyzed based on madness theory by Michel Foucault. The data had been taken from some sentences and paragraphs from the trilogy. The study design was the descriptive qualitative method. The results of this study indicated that there were three indicators of madness experienced by David through the trilogy, which were the existence of the elite, asylum and punishment. Mental and physical punishments were the effects of madness in David’s character through himself in the trilogy. Keywords: dave pelzer’s trilogy, madness.